The cultural influences of black nguni culture on water consumption and how they can assist the water crisis within the city of Cape Town - Sipamla, Sihle (The IIE, 2018)
Water resources are subject to increasing stress in many urban areas. Managing water consumption and supply are key issues for the sustainable development of cities. The development within the social and cultural background of consumers, have minor research attention given the impacts that the ethnic and cultural diversity of a population may have on water consumption. This thesis aimed to explore the ethnic and cultural correlates of water use, bridging the information gap regarding water use in cities. This is important since cultural mindsets and behaviour is a driver in group behaviour. The study employed Quantitative and qualitative research techniques to analysis water use and conservation attitudes and behaviours among the Black community within Cape Town. With identification that disparities exist across the ethnic groups in pro-environmental water attitudes, behaviours and daily water use practices with influence of ethnic factors on pro-conservational behaviours and water consumption being significant. Even greater than socio-demographic factors including household size and income, diverse understanding of water issues in English and ethnic backgrounds, the different habits, routines and considerations relating to water use across ethnic groups, are important in understanding the ethnic effects on water use. Results highlighted the importance of including ethnicity and cultural sensitivity issues into the process of decision making regarding environmental management. Adding significance to understanding water consumption by ethnic groups, and important implications for water planning and management regarding cultural sensitivity.
Keywords: Water consumption; Culture; Diversity; Ethnicity; Sustainable development